Analysis of prostate needle biopsy in patients visiting B & B hospital: a three year retrospective study - Baidya, R; Sigdel, B; Shrestha, S; Baidya, NL (Journal of Pathology of Nepal, 2013)
Background: Prostate cancer is the most common cancer in men. Prostate specifi c antigen is a key tumor marker to screen for prostate cancer. However, controversy exits regarding the impact of prostate cancer screening. Materials and Methods: This was a retrospective study carried out in the Department of Histopathology of B and B Hospital during a period of 2 years from 01-05-2064 to 01-05-2066. The study included 26 cases of prostate needle biopsy specimens. Results: The more common age group (43.9%) was 70-79 years followed by the age group above 80 years old (7.5%). The most common benign lesion observed was benign prostatic hyperplasia (5 out of 11, 45.45%), followed by benign prostatic hyperplasia with chronic prostatitis (3 out of 11, 27.27%). The most common malignant types of lesion encountered was prostatic adenocarcinoma with an incidence of 84.62% (11 out of 13 cases), following nodular hyperplasia of prostate with low grade prostatic intraepithelial neoplasm 15.38% (2 out of 13 cases). Among the benign and the malignant cases serum PSA ranged from 0 - ?10.1 ng/ml. Conclusion: Serum PSA value has signifi cant role in the diagnosis of malignant prostatic lesions. However, Histological diagnosis still remains the gold standard for the diagnosis of prostatic cancer. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 394-396 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7865